Physical properties of asphalt binder modified using plastic waste - Ahmad, Faradillah; Mamat, Rosmawati; Mad Rosni, Nurul Najihah; Shaffie, Ekarizan; Kamaluddin, Noor Azreena; Hashim, Wardati (Faculty of Civil Engineering, 2026)
The issue of managing plastic waste has become a serious global concern, driving researchers to explore practical and sustainable recycling alternatives. One promising approach is incorporating plastic waste into asphalt binders for road construction. This study aims to evaluate the physical characteristics of asphalt binders modified with plastic waste polymers, specifically Low-Density Polyethylene (LDPE) and Polystyrene (PS), to enhance pavement performance while supporting environmental sustainability. In this research, different proportions of plastic waste (2%, 6%, and 10%) were blended with conventional 60/70 penetration grade bitumen using the wet mixing method. The modified binders were then tested for penetration and softening point according to Malaysian Standard (MS 124). The results showed that plastic modification reduced penetration values and increased softening points, indicating higher stiffness and improved resistance to high temperatures. Among the modifiers, LDPE exhibited the most significant improvement, while the PS+LDPE blend provided a balanced performance between flexibility and strength. These findings align with previous studies which reported that polymer-modified bitumen improves thermal stability and rutting resistance. Overall, the study demonstrates that the use of plastic waste as a bitumen modifier enhances the performance of asphalt binder and contributes to more sustainable road pavement development.